2021
DOI: 10.20527/es.v17i1.11351
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Arang Aktif Cangkang Kelapa Sawit Teraktivasi H3PO4 untuk Penurunan Kadar Besi (Fe), Mangan (Mn) dan Kondisi pH pada Air Asam Tambang

Abstract: Acid mine drainage is water containing dissolved metals such as iron (Fe), manganese (Mn), and other sulfate compounds. It causes various impacts such as environmental pollution, reducing soil fertility, disrupting the health of surrounding communities, and causes the corrosion of mining equipment. The adsorption method is used to reduce the concentration of heavy metals from liquid waste. Activated carbon of palm shell can be used as a heavy metal adsorbent in acid mine drainage. The research aims to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The carbon of the palm kernel shell before activation still contains tar and other substances, so that the ashing process produces a higher ash content. The resulting volatile matter content (14.31%) is in accordance with the results of previous studies using activated carbon of 100 mesh palm kernel shells and 5% H3PO4 activated [20]. Measurement of volatile matter content on activated carbon of palm kernel shells activated by NaOH with a carbonization temperature of 400 -600 o C obtained volatile matter levels of 10 -15% [26].…”
Section: Characteristic Of Activated Carbonsupporting
confidence: 88%
See 3 more Smart Citations
“…The carbon of the palm kernel shell before activation still contains tar and other substances, so that the ashing process produces a higher ash content. The resulting volatile matter content (14.31%) is in accordance with the results of previous studies using activated carbon of 100 mesh palm kernel shells and 5% H3PO4 activated [20]. Measurement of volatile matter content on activated carbon of palm kernel shells activated by NaOH with a carbonization temperature of 400 -600 o C obtained volatile matter levels of 10 -15% [26].…”
Section: Characteristic Of Activated Carbonsupporting
confidence: 88%
“…The oil palm shells are washed thoroughly with distilled water and dried in the sun until dry (empty weight). Authoring uses a furnace at 650 o C for 2 hours [20]. Charcoal is crushed and sieved with passing size of 50 and 100 mesh to get particle size < 0.150 -0.300 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study conducted by Hendra reported that the highest quality absorbent could be made from palm kernel shell at a temperature of 850 o C [8]. In order to increase the adsorbent's adsorption capacities and efficiency, chemicals including phosphate acid (H3PO4) [9], chloric acid (HCl) [10], sodium hydroxide (NaOH), and potassium hydrogen oxide (KOH) [11] have also been used in the activation process. Specifically, H3PO4 activator has shown the ability to effectively produce chemical reactions in the synthesis of organic compounds [12], increasing final product yield to ensure better adsorption with enhanced physical and chemical stability.…”
Section: Introductionmentioning
confidence: 99%